1985
DOI: 10.2508/chikusan.56.122
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Breed, Sex and Anatomical Location on Lipid and Fatty Acid Composition of Bovine Intermuscular Fat

Abstract: Thirty-one animals including Japanese Black (9 steers), Holstein (8 steers examine the effects of breed, sex and anatomical location on the lipid and fatty acid composition of intermuscular fat in the carcasses at a constant slaughter weight, Intermuscular fat samples were taken from the shoulder, loin, rump, brisket and flank regions of each carcass, respectively. Total lipid content was significantly affected by breed and location. Japanese Black had a greater total lipid content than other breeds. Of locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…These studies have confirmed that the fat of heifers tends to be more unsaturated than the fat of steers (Yoshimura and Namikawa, 1985;Zembayashi et al, 1995) and aging increases MUFA (Huerta-Leidenz et al, 1996). Furthermore, effects of breed differences are also reported; purebred Wagyu cattle or the other breeds derived from Wagyu generally tend to have higher proportions of unsaturated fatty acids than other breeds (Yoshimura and Namikawa, 1985;May et al, 1993). Inoue et al (2008) used field data from heifers and steers with an average slaughter age of 31.6 months.…”
Section: Phenotypic Measurementsmentioning
confidence: 84%
See 2 more Smart Citations
“…These studies have confirmed that the fat of heifers tends to be more unsaturated than the fat of steers (Yoshimura and Namikawa, 1985;Zembayashi et al, 1995) and aging increases MUFA (Huerta-Leidenz et al, 1996). Furthermore, effects of breed differences are also reported; purebred Wagyu cattle or the other breeds derived from Wagyu generally tend to have higher proportions of unsaturated fatty acids than other breeds (Yoshimura and Namikawa, 1985;May et al, 1993). Inoue et al (2008) used field data from heifers and steers with an average slaughter age of 31.6 months.…”
Section: Phenotypic Measurementsmentioning
confidence: 84%
“…Fatty acid composition is influenced by sex (Yoshimura and Namikawa, 1985;Zembayashi et al, 1995), diet (Melton et al, 1982;Mandell et al, 1998) and age (Huerta-Leidenz et al, 1996). Genetic influences, such as breed (Yoshimura and Namikawa, 1985;May et al, 1993) and sire (Xie et al, 1996), have also been reported, including sire-based differentiation in Japanese Black cattle (Oka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also determined the contents of C18:1 as 53.6% and MUFA as 57.8%, smaller values than in the present study (C18:1, 54.4%; MUFA, 63.7%). It is known that the degree of unsaturation is higher in heifers than in steers (Yoshimura & Namikawa ; Zembayashi et al ; Inoue et al , ) and increases with aging (Ishida et al ; Inoue et al ). The higher percentages of C18:1 and MUFA found in our study could be due to the high proportion of heifers in the data analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The quantity and composition of lipid in depot fat of meat are regarded as important factors influencing meat and carcass quality2, 3,8,10,12,13) The characteristics of triacylglycerol, being the major component of intramuscular fat of beef, affect the flavor of beef9). Determinations of fatty acid compositions2,4-7), carbon number distributions5-7) and stereospecific position of acyl groups4,5) of triacylglycerol from fat had been carried out for the analysis of chemical characteristics of triacylglycerol, while there were few reports on the molecular species compositions of triacylglycerols isolated from muscle of Japanese beef cattle.…”
mentioning
confidence: 99%